Efficacy of digitalized comprehensive educational program for patients with allergic contact dermatitis: A randomized controlled trial - Viarasilpa, Wongsiya; Sittiwattanawong, Prattana (Chulalongkorn Medical Journal, 2022)
Background: Allergic contact dermatitis (ACD) is an inflammatory skin disease resulting from exposure to allergen. The patient education is crucial to successful treatment and management of ACD. However, this process can be time consuming, requiring trained healthcare personnel resulting in increased workload and may be difficult in the setting of limited workforce or resource. Objective: To assess the effect of informative digitalized video-based educational program (iDVE) on patients’ quality of life, disease severity and knowledge of ACD compared to standard counselling (control). Methods: Patients with ACD were randomized to participate in iDVE or control group. The primary outcome was the effect on patients’ quality of life using dermatology life quality index (DLQI) score at initial and follow-up visits at 1-month, 3-months and 6-months. The secondary outcomes were disease severity using eczema area and severity index (EASI) score and the scoring atopic dermatitis (SCORAD) score, patients’ knowledge and confidence at initial and each follow-up visits compared to control. Results: Seventy-four patients were enrolled, of which 38 patients were allocated to iDVE group and 36 to control group. At 3-month and 6-month follow-up, there were significant changes of DLQI from baseline in iDVE compared to control group (- 7.00 6.73 vs. - 3.56 7.29, P = 0.047; and - 9.03 7.36 vs. - 4.18 7.51, P = 0.01, respectively). DLQI at 6-months in iDVE group was also significantly lower compared to control (2.47 3.66 vs. 5.27 5.85, P = 0.023). Conclusion: The informative digitalized video-based educational program can significantly improve patients’ quality of life and may has positive impact on disease severity and patients’ knowledge regarding allergic contact dermatitis.